Visualization of image distortion on camera calibration for stereo vision application - Hamzah, Rostam Affendi; Abd Ghani, Shamsul Fakhar; Din, Asri; A Aziz, Khairul Azha (2012)
This paper presents a visualization of image distortion on camera calibration for stereo vision application. The 3D image plane in a group of target or image during the process of stereo pair calibration is also discussed. The extrinsic parameters of camera calibration can be viewed in 3D image or scene which contains the rotation and translation of vector. The error re-projection of a single image could determine the less error of distortion during the extraction of chessboard corner each image taken. The distortion model also generates an error coordinate system in pixel value. The 3D image will viewed the result and output of extrinsic parameters during the calibration process.